Stigma towards people with mental disorders and its components – a perspective from multi-ethnic Singapore. (28th March 2016) - Subramaniam, M.; Abdin, E.; Picco, L.; Pang, S.; Shafie, S.; Vaingankar, J. A.; Kwok, K. W.; Verma, K.; Chong, S. A.
Abstract : Aims: The current study aimed to: (i) describe the extent of overall stigma as well as the differences in stigma towards people with alcohol abuse, dementia, depression, schizophrenia and obsessive compulsive disorder, as well as (ii) establish the dimensions of stigma and examine its correlates, in the general population of Singapore, using a vignette approach. Methods: Data for the current study came from a larger nation-wide cross-sectional study of mental health literacy conducted in Singapore. The study population comprised Singapore Residents (Singapore Citizens and Permanent Residents) aged 18–65 years who were living in Singapore at the time of the survey. All respondents were administered the Personal and Perceived scales of the Depression Stigma scale and the Social Distance scale to measure personal stigma and social distance, respectively. Weighted mean and standard error of the mean were calculated for continuous variables, and frequencies and percentages for categorical variables. Exploratory structural equation modelling and confirmatory factor analysis were used to establish the dimensions of stigma. Multivariable linear regressions were conducted to examine factors associated with each of the stigma scale scores. Results: The mean age of the respondents was 40.9 years and gender was equally represented (50.9% were males). The findings from the factor analysis revealed that personal stigma formed two distinct dimensions comprising 'weak-not-sick' and 'dangerous/unpredictable' while social distance stigma items loaded strongly into a single factor. Those of Malay and Indian ethnicity, lower education, lower income status and those who were administered the depression and alcohol abuse vignette were significantly associated with higher weak-not-sick scores. Those of Indian ethnicity, 6 years of education and below, lower income status and those who were administered the alcohol abuse vignette were significantly associated with higher dangerous/unpredictable scores. Those administered the alcohol abuse vignette were associated with higher social distance scores. Conclusion: This population-wide study found significant stigma towards people with mental illness and identified specific groups who have more stigmatising attitudes. The study also found that having a friend or family member with similar problems was associated with having lower personal as well as social distance stigma. There is a need for well-planned and culturally relevant anti-stigma campaigns in this population that take into consideration the findings of this study.